2018 IEEE Wireless Communications and Networking Conference (WCNC) 2018
DOI: 10.1109/wcnc.2018.8377395
|View full text |Cite
|
Sign up to set email alerts
|

Improving wireless multicast communications with NC: Performance assessment over a COTS platform

Abstract: Multicast services are believed to play a relevant role in next wireless networking scenarios. In this paper we exploit Tunable Sparse Network Coding techniques to increase reliability of multicast communications. We show that the proposed network coding scheme yields a better performance than state-of-the-art solutions, which are traditionally based on retransmissions. We first use a model to analytically compare the two approaches. Then, we validate and broaden this analysis by means of an experimental campa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…4. To calculate delivery rate, (4) is used for the leader probability and (10)- (12) have been used for the probability of leader transmissions, then the differential knowledge probabilities are given by (13), (14) and the delivery rate is given by (3). In all settings, it is observed that the users in group H have reached the delivery rate of λ, and for the users in L, there is a reasonable match between the simulation and analytical results.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…4. To calculate delivery rate, (4) is used for the leader probability and (10)- (12) have been used for the probability of leader transmissions, then the differential knowledge probabilities are given by (13), (14) and the delivery rate is given by (3). In all settings, it is observed that the users in group H have reached the delivery rate of λ, and for the users in L, there is a reasonable match between the simulation and analytical results.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Note that the summation in (13) represents the probability that U i has not seen the requested packet by U h while U h has been the leader. Similarly, in (14) when H = Ø, the summation is the same probability while U l has been the leader.…”
Section: B Probability Of Differential Knowledge For the Users In Lmentioning
confidence: 99%
See 2 more Smart Citations